META ANALISIS: PENDIDIKAN KARAKTER PADA ANAK USIA SEKOLAH DASAR - Puput Wahyu Hidayat; Zulqoidi R Habibie; DAFIT AFIANTO (Jurnal Tunas Pendidikan, 2022)
Character education is one of the things that must be done and instilled at elementary school age. In this article, we will discuss various character education carried out in all regions in Indonesia, especially at elementary school age. The study used a meta-analysis by reviewing 15 articles. This type of research used qualitative research. The development of the current era makes it easier for students to access the internet without limits, so that elementary school age must be guided in carrying out all activities, both at home and at school. So that children who can be properly supervised will have good character as well. The control of parents and teachers in this case is very to order. Character education is carried out so that students can be directed in development, so that they become children who have a sense of responsibility, are creative, fear God and become the next generation of the nation that can be relied on. The results showed that, from the articles analyzed, all students in elementary schools had implemented character learning well, which was assisted by teachers at school and supported by parents at home.